Economic Growth and Greenhouse Gas Emissions in Asia: A Dynamic Panel Analysis Across Income Groups - Nugroho, Hari (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study contributes to environmental economics by examining the relationship between economic growth and greenhouse gas emissions across Asian countries, while accounting for differences in income levels. Using a dynamic STIRPAT framework, the analysis also incorporates urbanization, energy intensity, and carbon intensity to understand how emission drivers vary across stages of development. Research Objectives: The study aims to explore the dynamic link between economic growth and greenhouse gas emissions and to identify how demographic and technological factors influence emission patterns in lower-middle-, upper-middle-, and high-income Asian economies. Research Methods: The analysis uses panel data from 41 Asian countries during 1990–2022 and applies a dynamic panel estimation method, the two-step System Generalized Method of Moments (System-GMM). Empirical Results: Economic growth and urbanization generally increase greenhouse gas emissions. However, the main drivers differ by income level. In lower-middle-income countries, emissions are mainly driven by economic growth and carbon intensity. In upper-middle-income countries, urbanization and energy intensity play a larger role, while in high-income countries, the link between growth and emissions becomes weaker. Implications: These findings suggest that environmental policies should be tailored to each stage of economic development. JEL Classification: C23, Q56, O44, Q43